Research Trend In The Field of Work Setting During Covid-19 : A Bibliometric Analysis - Stefanus Rumangkit; AK Yohansson; Lukmanul Hakim (Proceeding International Conference on Information Technology and Business, 2020)
This article had a purpose to identify research themes related to work settings during the Covid-19 pandemic. The benefit of this research was to provide an overview of research related to work settings in the future. The approach in this study used bibliometric analysis. In the first stage, a search for articles with the keywords work setting and Covid-19 was carried out, with the search year 2020. Furthermore, there were found as many as 458 articles sourced from Elsevier data. After obtaining the article data, the researcher used the VOSviewer software to describe the research work setting. This article showed that there were 7 clusters in the latest work setting research, namely: Cluster 1 consisted of clinical work, depression, disability, feasibility, hospitality setting, mental health, physical activity, sick leave, and workability. Cluster 2 consisted of autonomy, emotional exhaustion, recovery experience, social support, stress, work characteristics, work management. Cluster 3 was included burnout, career, happiness, job satisfaction, work environment, work-life balance, and workplace violation. Cluster 4 consisted of complexity, identity work, motivation, self-care, and workload. Cluster 5 consisted of cognitive problems, communication technology, social work, and social workers. Cluster 6 covered a commitment organization, Equal pay, productivity, and workshops. Cluster 7 were income, supervisor, and wellness.Keywords: Work Setting; Work Situation; Pandemic; Covid-19; Bibliometric